A Magnetofluorescent Carbon Dot Assembly as an Acidic H2O2‐Driven Oxygenerator to Regulate Tumor Hypoxia for Simultaneous Bimodal Imaging and Enhanced Photodynamic Therapy. Issue 13 (13th February 2018) - Jia, Qingyan; Ge, Jiechao; Liu, Weimin; Zheng, Xiuli; Chen, Shiqing; Wen, Yongmei; Zhang, Hongyan; Wang, Pengfei
Abstract: Recent studies indicate that carbon dots (CDs) can efficiently generate singlet oxygen ( 1 O2 ) for photodynamic therapy (PDT) of cancer. However, the hypoxic tumor microenvironment and rapid consumption of oxygen in the PDT process will severely limit therapeutic effects of CDs due to the oxygen‐dependent PDT. Thus, it is becoming particularly important to develop a novel CD as an in situ tumor oxygenerator for overcoming hypoxia and substantially enhancing the PDT efficacy. Herein, for the first time, magnetofluorescent Mn‐CDs are successfully prepared using manganese(II) phthalocyanine as a precursor. After cooperative self‐assembly with DSPE‐PEG, the obtained Mn‐CD assembly can be applied as a smart contrast agent for both near‐infrared fluorescence (FL) (maximum peak at 745 nm) and T 1 ‐weighted magnetic resonance (MR) (relaxivity value of 6.97 mM −1 s −1 ) imaging. More interestingly, the Mn‐CD assembly can not only effectively produce 1 O2 (quantum yield of 0.40) but also highly catalyze H2 O2 to generate oxygen. These collective properties of the Mn‐CD assembly enable it to be utilized as an acidic H2 O2 ‐driven oxygenerator to increase the oxygen concentration in hypoxic solid tumors for simultaneous bimodal FL/MR imaging and enhanced PDT. This work explores a new biomedical use of CDs and provides a versatile carbon nanomaterial candidate for multifunctional nanotheranostic applications. Abstract : A magnetofluorescent Mn‐CD assembly is designed and prepared as an acidic H2 O2 ‐driven oxygenerator to regulate the hypoxic tumor microenvironment for simultaneous bimodal fluorescence/ T 1 ‐weighted magnetic resonance imaging and enhanced photodynamic therapy of solid tumors. This work demonstrates a new biomedical use of CDs and provides a versatile carbon nanomaterial candidate for multifunctional nanotheranostic applications.